Hubungan usia dan hipertensi terhadap kejadian BPH di RSUD. Dr. H. Abdul Moeloek tahun 2020 - Elsa Rizki Lilian; Andi Siswandi; Anggunan Anggunan (Universitas Malahayati, 2021)
ABSTRACT: THE CORRELATIONS OF AGE AND HYPERTENSION WITH THE OCCURRENCE OF BPH IN THE SURGICAL WARD AT RSUD DR.H.ABDUL MOELOEK IN 2020Introduction: Lower Urinary Tractus Symptoms (LUTS) is a problem that is experienced by men around the world and one that often occurs is Benign prostate hyperplasia (BPH). BPH is a histological disorder characterized by the proliferation of prostate cells. It is estimated that 50% of men show BPH histopathology at the age of 60 years old and an increase of 90% at the age of 80 years old. Hypertension is also known to have a role in increasing prostate volume, in a cohort study it was found that hypertension resulted in an increased risk of 1.5 times to cause LUTS/BPH.Objective: To determine the relationship between age and hypertension on the incidence of BPH in Dr. H. Abdul Moeloek in 2020.Methods: This study is quantitative research, an observative analytic study design with a cross-sectional approach was carried out at RSUD Dr. H. Abdul Moeloek which was taken on October 16, 2020. The population was all patients in the Surgical Ward with total sampling. Data collection was obtained from secondary data from medical records. Data analysis was performed Univariate analysis (frequency distribution) and bivariate analysis with chi-square.Results: Respondents with BPH aged >50 years old were 32 respondents (97%) and respondents with BPH and hypertension were 20 respondents (60.6%). The results of the bivariate analysis using chi-square showed a significant relationship between BPH and age p value=0.000 (P<0.05) and the relationship between BPH and hypertension with p value=0.000 (p<0.05).Conclusion: There is a significant relationship between BPH with age and hypertension with the occurrence of BPH in the Surgical polyclinic at RSUD Dr.H.Abdul Moeloek in 2020. Keywords: BPH, Age, Hypertension INTISARI: HUBUNGAN USIA DAN HIPERTENSI TERHADAP KEJADIAN BPH DI RSUD Dr.H.ABDUL MOELOEK Pendahuluan: Lower Urinary Tractus Symptoms (LUTS) adalah masalah yang banyak dialami oleh laki-laki di seluruh dunia dan salah satu yang sering terjadi adalah Benigna Prostat Hyperplasia (BPH). BPH adalah kelainan histologis yang khas di tandai dengan proliferasi sel-sel prostat. Diperkirakan 50% laki-laki menunjukan histopatologi BPH pada umur 60 tahun dan meningkat 90% pada umur 80 tahun Hipertensi juga diketahui memiliki peranan dalam peningkatan volume prostat yakni pada suatu penelitian cohort diketahui adanya hipertensi mengakibatkan peningkatan resiko sebanyak 1,5 kali untuk menimbulkan gejala LUTS/BPH.Tujuan: Untuk mengetahui adanya hubungan usia dan hipertensi terhadap kejadian BPH di RSUD Dr. H. Abdul Moeloek Tahun 2020Metode: Jenis penelitian kuantitatif, rancangan penelitian analitik observatif dengan pendekatan cross sectional telah dilakukan di RSUD Dr.H.Abdul Moeloek Provinsi Lampung yang berlangsung pada 16 Oktober 2020. Populasi adalah seluruh pasien di Poli Bedah dengan pengambilan sampel secara total sampling. Pengumpulan data diperoleh dari data sekunder yang diperoleh dari rekam medis. Analisis data secara univariat (distribusi frekuensi) dan uji bivariat mengunakan chi squareHasil: Responden dengan BPH yang berusia >50 tahun sebanyak 32 responden (97%) dan responden dengan BPH dengan hipertensi sebanyak 20 responden (60,6%). Hasil Uji bivariat menggunakan chi square menunjukkan adanya hubungan signifikan antara BPH dengan usia diperoleh nilai p=0,000 (P<0,05) dan hubungan BPH dengan hipertensi nilai p=0,000 (p<0,05).Kesimpulan: Terdapat hubungan signifikan antara BPH dengan usia dan terdapat hubungan sgnifikan antara BPH dengan hipertensi di poli klinik bedah RSUD Dr.H.Abdul Moeloek tahun 2020.Kata kunci: BPH, Usia, Hipertensi